Investigating dose finding methods and different priors in Bayesian continual reassessment method - Tuba Koc; Mehmet Ali Cengiz (Kuwait Journal of Science)
Clinical trials are studies that explore whether a treatment, drug or device is safe and effective for humans. These studies can show which medial method work best for certain diseases. A well-designed and a properly-analyzed clinical trial is a powerful tool for the development of new drugs. The first step in drug discovery (phase I) is very important to determine maximum tolerated dose (MTD).